Human Trafficking: Results of a 5-Year Theory-Based Evaluation of Interventions to Prevent Trafficking of Women From South Asia - Zimmerman, Cathy; Mak, Joelle; Pocock, Nicola S.; Kiss, Ligia (Frontiers in Public Health, 2021)
Preventing modern slavery is of global interest, but evidence on interventions remains weak. This paper presents findings from a 5-year theory-based evaluation of an empowerment and knowledge-building intervention to prevent the exploitation of South Asian female migrant workers. The evaluation used realist evaluation techniques to examine the intervention mechanisms, outcomes, and context. Findings from qualitative and quantitative data from Nepal, India, and Bangladesh indicate that the intervention mechanisms (trainings) were not well-targeted, not delivered by appropriate trainers, and did not address participants' expectations or concerns. The outcomes of empowerment and migration knowledge were not achieved due to poor integration of context-related factors, flawed assumptions about the power inequalities, including barriers preventing women from asserting their rights. Ultimately, interventions to prevent exploitation of migrant workers should be developed based on strong evidence about the social, political, and economic realities of their migration context, especially in destination settings.